Digital Ethics and Public Trust in the Era of Government Digital Transformation - Adelia, Elza; Haliah; Andi Kusumawati (Cita konsultindo, 2025)
This study explores the critical intersection between digital ethics and public trust within the context of government digital transformation. As governments increasingly adopt digital technologies to streamline public services, ethical challenges have emerged—ranging from data privacy violations and algorithmic opacity to excluding marginalized groups from digital access. These ethical dilemmas can significantly undermine citizens' confidence in government institutions if left unaddressed. This study identifies core themes and ethical concerns that influence public perception and trust through a Systematic Literature Review (SLR) of scholarly articles published between 2010 and 2024. The findings reveal that ethical misalignments in digital initiatives—particularly concerning transparency, accountability, and inclusivity—can erode institutional legitimacy. Conversely, when digital ethics are embedded into governance structures and service designs from the outset, they can enhance citizen engagement, foster social equity, and strengthen institutional trust. This study highlights the urgent need for public institutions to adopt ethics-by-design frameworks, prioritize participatory digital policy-making, and invest in inclusive digital literacy initiatives to ensure that technological progress in governance is effective and equitable.